ALG1-CDG Caused by Non-functional Alternative Splicing Involving a Novel Pathogenic Complex Allele - González-Domínguez, Carlos Alberto; Fiesco-Roa, Moisés O.; Gómez-Carmona, Samuel; Kleinert-Altamirano, Anke Paula Ingrid; He, Miao; Daniel, Earnest James Paul; Raymond, Kimiyo M.; Abreu-González, Melania; Manrique-Hernández, Sandra; González-Jaimes, Ana; Salinas-Marín, Roberta; Molina-Garay, Carolina; et al. (Frontiers in Genetics, 2021)
We report on a Mexican mestizo patient with a multi-systemic syndrome including neurological involvement and a type I serum transferrin profile. Clinical exome sequencing revealed complex alleles in ALG1, the encoding gene for the chitobiosyldiphosphodolichol beta-mannosyltransferase that participates in the formation of the dolichol-pyrophosphate-GlcNAc(2)-Man(5) a lipid-linked glycan intermediate during N-glycan synthesis. The identified complex alleles were NM_019109.5(ALG1): c.[208+16_208+19dup; 208+25G>T] and NM_019109.5(ALG1): c.[208+16_208+19dup; 1312C>T]. Although both alleles carried the benign variant c.208+16_208+19dup, one allele carried a known ALG1 pathogenic variant (c.1312C>T), while the other carried a new uncharacterized variant (c.208+25G>T) causing non-functional alternative splicing that in conjunction with the benign variant define the pathogenic protein effect (p.N70S_S71ins9). The presence in the patient’s serum of the pathognomonic N-linked mannose-deprived tetrasaccharide marker for ALG1-CDG (Neu5Acα2,6Galβ1,4-GlcNAcβ1,4GlcNAc) further supported this diagnosis. This is the first report of an ALG1-CDG patient from Latin America.